2004
DOI: 10.1097/01.alc.0000139814.81811.62
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functioning Early in Abstinence From Alcohol

Abstract: Background: Executive dysfunction is among the cognitive impairments that may persist after abstinence in alcohol-dependent persons. The type(s) and extent of executive dysfunction early in abstinence have not been well characterized, but they may have important implications for the evolution of behavioral treatment strategies.Methods: To determine which aspects of executive functioning were impaired in early abstinence, we administered memory and executive function tests to veterans who successively presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
80
4
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 71 publications
3
80
4
2
Order By: Relevance
“…In the literature, there is not always a relation between sobriety period and neurocognitive test performances [29][30][31]. In our study, no significance found between the relapsed and protracted sober groups for the Stroop test performances.…”
Section: Discussioncontrasting
confidence: 70%
“…In the literature, there is not always a relation between sobriety period and neurocognitive test performances [29][30][31]. In our study, no significance found between the relapsed and protracted sober groups for the Stroop test performances.…”
Section: Discussioncontrasting
confidence: 70%
“…Recent studies have suggested that cognitive status may play a role in treatment efficacy (Miller, 1991;Gottschalk et al, 2001;Aharonovic et al, 2003;Teichner et al, 2002). Thus, the deficits we have demonstrated in both MMT and PA patients suggest that these populations may benefit from more personal effectiveness programs, adult daily living skills, remedial education programs, and concrete treatment planning to improve outcomes (Czuchry and Dansereau, 2004;Zinn et al, 2004).…”
Section: Discussionmentioning
confidence: 75%
“…El alcohol consumido de forma aguda provoca deterioro de las funciones cognitivas (Weissenborn y Duka, 2003) y este deterioro puede persistir en las fases iniciales de la abstinencia alcohólica (Zinn, Stein y Swartzwelder, 2004), lo cual nos ayuda a comprender la causa de que nuestros datos muestren un deterioro cognitivo en jóvenes cuya historia de consumo no es tan dilatada en el tiempo, equivalente al encontrado en consumidores crónicos con una historia de consumo de duración mucho mayor. Además, diversos estudios ponen de manifiesto que los adolescentes, cuyo cerebro esta aún en desarrollo y por tanto es más vulnerable, son más sensibles que los adultos a una gran parte de los efectos del alcohol, incluido el deterioro de los procesos cognitivos, especialmente, la memoria y el aprendizaje, y que esos efectos pueden continuar en la etapa adulta incluso habiendo dejado de consumir alcohol (Crews, Braun, Hoplight, Switzer y Knaapp;2000;Crews et al, 2000;HillerSturmhofel y Swartzwelder, 2004;Tokunaga, Silvers y Matthews, 2006;Yttri, Buro y Hunt, 2004).…”
Section: Discussionunclassified